2021
DOI: 10.1038/s41396-021-01028-3
|View full text |Cite
|
Sign up to set email alerts
|

Reductive dissolution of pyrite by methanogenic archaea

Abstract: The formation and fate of pyrite (FeS2) modulates global iron, sulfur, carbon, and oxygen biogeochemical cycles and has done so since early in Earth’s geological history. A longstanding paradigm is that FeS2 is stable at low temperature and is unavailable to microorganisms in the absence of oxygen and oxidative weathering. Here, we show that methanogens can catalyze the reductive dissolution of FeS2 at low temperature (≤38 °C) and utilize dissolution products to meet cellular iron and sulfur demands associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 38 publications
5
54
1
Order By: Relevance
“…Recent studies have shown that methanogens can reductively dissolve FeS 2 ( Payne et al, 2021a , b ). Given that (1) methanogens can produce H 2 during methanogenesis ( Lupa et al, 2008 ; Kulkarni et al, 2018 ) combined with (2) prior studies that have demonstrated abiotic FeS 2 reduction by H 2 , albeit at high temperature (>90°C) and high H 2 partial pressure (>8 bar, equivalent to >7 mM aqueous H 2 ; Truche et al, 2010 ), it was necessary to first evaluate the potential for H 2 to abiotically reduce FeS 2 at lower temperature.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have shown that methanogens can reductively dissolve FeS 2 ( Payne et al, 2021a , b ). Given that (1) methanogens can produce H 2 during methanogenesis ( Lupa et al, 2008 ; Kulkarni et al, 2018 ) combined with (2) prior studies that have demonstrated abiotic FeS 2 reduction by H 2 , albeit at high temperature (>90°C) and high H 2 partial pressure (>8 bar, equivalent to >7 mM aqueous H 2 ; Truche et al, 2010 ), it was necessary to first evaluate the potential for H 2 to abiotically reduce FeS 2 at lower temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, pure cultures of methanogenic archaea ( Methanosarcina barkeri strain MS and Methanococcus voltae strain A3) were shown to catalyze the reductive dissolution of FeS 2 when grown with methanol and acetate or with formate, respectively, when incubated at 38°C, with FeS 2 as the sole source of Fe and S for cell growth ( Payne et al, 2021b ). This same study showed that M. voltae required direct contact with FeS 2 to catalyze its reduction and/or to acquire Fe and S dissolution products to meet nutritional demands.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations